Effect of phase change material wall on natural convection heat transfer inside an air filled enclosure. (5th November 2017) - Labihi, Abdelouhab; Aitlahbib, Faiçal; Chehouani, Hassan; Benhamou, Brahim; Ouikhalfan, Mohammed; Croitoru, Cristiana; Nastase, Ilinca
Highlights: An air cavity with one side made of PCM is studied numerically and experimentally. The model describes the coupled flow and heat transfer in cavity and the PCM layer. The heat transfer in the cavity is affected notably when the phase change occurs. The volume variation during the phase change affects the simulation accuracy. A new approach based on the volume contraction during solidification is proposed. Abstract: This paper deals with a numerical and experimental study of a square enclosure filled with air and differentially heated. The heated vertical wall of the enclosure contains a 1 cm thickness layer of a phase change material (PCM), whereas the opposite one is cooled. The dimensions of the experimental air cavity are 10 cm × 10 cm with a width of 10 cm. The PCM layer, initially molten, is discharged in the air within the cavity. Temperature measurements were performed inside the air cavity as well as the PCM and the PCM/air interface during the charging and discharging processes. A numerical model based on the coupled Navier-Stokes and energy equations for the air inside the cavity and the PCM layer was developed to examine the perturbation of the phase change on heat transfer at the PCM/air interface. The results showed a notable disagreement between the calculated and measured temperature in the cavity and PCM, when the density change during the solidification process has not been taken into account. A new approach based on volume contraction during solidification has been proposed and successfully tested to overcome this issue. Moreover, the simulations demonstrated that the heat transfer in the cavity is affected significantly when the phase change occurs.